2021
DOI: 10.21203/rs.3.rs-820735/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers and Facilitative Factors in the Implementation of Workplace Health Promotion Activities in Small and Medium-Sized Enterprises: A Qualitative Study

Abstract: Background: It is reasonable to target small and medium-sized enterprises (SMEs) as a workplace to promote the implementation of evidence-based interventions (EBIs) for reducing health inequalities. Previous literature reveals various barriers that SMEs face during implementation, such as a lack of time, accessibility, and resources. However, few studies have comprehensively examined those influential factors at multi-levels. This study aims to identify the factors influencing the implementation of non-communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This study protocol will apply the specific implementation strategy wherein researchers meet with employers/managers online for 30-45 minutes to encourage them to invite employees to participate in the "WellBe-LINE" Program. This strategy is based on previous findings of leadership engagement being a considerable barrier in the health program implementation (7). Furthermore, PPI partners who engaged in all research stages will provide essential suggestions in implementation, leading to a positive impact on field-specific studies (65).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study protocol will apply the specific implementation strategy wherein researchers meet with employers/managers online for 30-45 minutes to encourage them to invite employees to participate in the "WellBe-LINE" Program. This strategy is based on previous findings of leadership engagement being a considerable barrier in the health program implementation (7). Furthermore, PPI partners who engaged in all research stages will provide essential suggestions in implementation, leading to a positive impact on field-specific studies (65).…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining agreement, researchers will provide 30-45 minutes of online semi-structured lectures (meetings) with employers and managers via zoom to determine the situation at the company and provide knowledge about behavioral changes and an effective way to invite employees for participation and attain high penetration. A previous qualitative study suggested that fundamental factors influencing the implementation of workplace health promotion in SMSEs entail the leadership engagement of employers (7). Table 1 presents and justifies the contents of the semi-structured lecture with implementation strategy specification guidelines introduced by Proctor et al (42) for each component.…”
Section: Online Meeting With Employers/managers (Implementation Strat...mentioning
confidence: 99%
See 1 more Smart Citation